Controlling factors of plant community composition with respect to the slope aspect gradient in the Qilian Mountains. Issue 9 (18th September 2019) - Qin, Yanyan; Adamowski, Jan F.; Deo, Ravinesh C.; Hu, Zeyong; Cao, Jianjun; Zhu, Meng; Feng, Qi
Abstract: Slope aspect can affect soil temperature and soil type distribution, which, in turn, is likely to influence plant community composition. Three Qilian mountains, located in the northeastern part of the Qinghai–Tibetan Plateau, China, with four distinct slope aspects including south‐facing (SF), southwest‐facing (SW), northwest‐facing (NW), and north‐facing (NF) slope aspects, were studied to investigate the impact of slope aspect on plant assemblages. The results indicated that the environmental conditions were favorable under the NF and NW slope aspects as the soil water, soil organic carbon (SOC), and soil total nitrogen (STN) contents were significantly higher, and soil temperature (ST) and soil bulk density (SBD) were significantly lower than under the SF and SW aspects. Under all slope aspects, however, SOC, STN, and soil total phosphate in the top 0.2 m of topsoil accounted for about 60% of its total quantity, to a soil depth of 0.6 m. The plant communities on the SF and SW slopes were found to be primarily composed of Poa pratensis, Potentilla anrisena, and Carex aridula . In contrast, the plant community on the NW slope was mainly composed of Kobresia humilis, Carex crebra, and Potentilla bifurca, while on the NF slope it was mainly composed of Picea crassifolia, Carex scabrirostris, and Polygonum macrophyllum . The order of the influence of environmental factors on species distributions was ST > SBD > sand > STN. Results suggest that the slope aspect has an important role in the regulation of the soil environment and plant assemblages and that ST and SBD were the main factors influencing plant community composition. Furthermore, evidence from this study suggests that these mountains will become increasingly vulnerable to global warming. Thus, the plant community composition on these mountains must be monitored continuously in order to allow for strategic adaptive management.